PROMOTING GLOBAL CITIZENSHIP EDUCATION WITH SCIENCE TEACHING AND ANALYSING THE WAY IT IS PERCEIVED BY STUDENTS AT SECONDARY LEVEL - Kumari, Swati; Sharma, Sapna; ., J (PEOPLE: International Journal of Social Sciences, 2018)
This case study in Dhanbad, India explores 25 grade 9 students’ learning outcomes on the basis of gender and background in Global Citizenship Education related topics of science and also their perceptions about the Global Citizenship Education. It is time that we should realize that education itself has little value if it is merely meant for entrance straightaway into a profession instead we have to value the fact that Education needs to be open to the process of interpretation and complex engagements that is brought by teachers and the pupil within learning relationships. To create opportunity for Global Citizenship Education schools should adopt analytical approaches in knowledge acquisition and incorporate ways of teaching which supports the development of global citizens in educational programs. The study also examines the discourse of international organisations in order to promote better understanding of Global Citizenship Education and the study indicates that international organisations have developed a powerful GCE discourse. We are living in highly interconnected and interdependent world where to determine our collective future, we need to acquire profound understanding of global developments and expand our global consciousness. Findings revealed the existence of difference in knowledge based, value based and citizenship based outcomes of rural and urban background students as well as gender based differences were also found.